1996
DOI: 10.1139/g96-012
|View full text |Cite
|
Sign up to set email alerts
|

Genomic relationships between Dasypyrum villosum (L.) Candargy and D. hordeaceum (Cosson et Durieu) Candargy

Abstract: The origin and genomic constitution of the tetraploid perennial species Dasypyrum hordeaceum (2n = 4x = 28) and its phylogenetic relationships with the annual diploid Dasypyrum villosum (2n = 2x = 14) have been investigated by comparing the two genomes using different methods. There is no apparent homology between the conventional or Giemsa C-banded karyotypes of the two Dasypyrum species, nor can the karyotype of D. hordeaceum be split up into two similar sets. Polymorphism within several chromosome pairs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…The data indicate that the pericentromeric regions of chromosome arms in both the D. breviaristatum and D. villosum genomes are similar, while distal regions show reduced homologies and contain D. breviaristatum-and D. villosum-specific DNA sequences. Our observations are consistent with the findings of De Pace et al (1992), who isolated a highly repeated DNA sequence (p380) specific to D. villosum that is located near the telomeres and is not present in the tetraploid species (Blanco et al 1996). Conversely, in the closely related I-genome Hordeum species H. vulgare and H. bulbosum (with similar DNA content to D. villosum) major differences in DNA occur in the pericentromeric regions, which remain unlabelled on H. vulgare chromosomes when H. bulbosum DNA is used as a probe (Anamthawat-Jónsson et al 1993).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The data indicate that the pericentromeric regions of chromosome arms in both the D. breviaristatum and D. villosum genomes are similar, while distal regions show reduced homologies and contain D. breviaristatum-and D. villosum-specific DNA sequences. Our observations are consistent with the findings of De Pace et al (1992), who isolated a highly repeated DNA sequence (p380) specific to D. villosum that is located near the telomeres and is not present in the tetraploid species (Blanco et al 1996). Conversely, in the closely related I-genome Hordeum species H. vulgare and H. bulbosum (with similar DNA content to D. villosum) major differences in DNA occur in the pericentromeric regions, which remain unlabelled on H. vulgare chromosomes when H. bulbosum DNA is used as a probe (Anamthawat-Jónsson et al 1993).…”
Section: Discussionsupporting
confidence: 92%
“…Linde-Laursen and , by comparison of C-banded characters, did not support an autoploid origin of the tetraploid based on D. villosum. Blanco et al (1996) also could not support an autoploid origin on the basis of chromosomal traits, although similar restriction patterns were present when genomic DNA from the two species was probed with lowcopy or plastid DNA sequences. It is clear that species within, and beyond, the Triticeae show high levels of synteny at the levels of gene or single-copy markers (Moore et al 1995), although the differences in their repetitive DNA may be substantial and of greater significance for evolution and speciation.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Earlier studies on the morphological characters (Frederiksen 1991), chromosomal pairing (Bothmer and Claesson 1990) and chromosomal banding (Blanco et al 1996;Linde-Laursen and Frederiksen 1991;Pignone et al 2000) demonstrated that the D. breviaristatum was not an autoploid of D. villosum. This also conWrmed by genomic in situ hybridization (GISH) studies (Blanco et al 1996;Galasso et al 1997;Yang et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…According to Love (1984), the genomic formula of tetraploid D. breviarisatatum would be VVVV, which is the same as that of D. villosum. Similarly, this view was supported by biochemical evidence, such as the phenotypes of glutamic-oxaloacetic-transaminase, superoxide dismutase, alcohol dehydrogenase and esterase isozyme systems (Blanco et al, 1996). However, cytogenetic evidence such as fluorescence in situ hybridization patterns (Galasso et al, 1997;Uslu et al, 1999) and Giemsa C-banded karyotype (Frederiksen, 1991) seemed to be opposed to this view.…”
Section: Phylogenetic Analysis Of the Dasypyrum γ-Gliadin Genesmentioning
confidence: 99%